Effect of Feeding Several Energy Sources on Carcass Production of Local Male Pigs in the Grower Phase - Seran, Alfiana; Klau Tahuk, Paulus; Purwantiningsih, Theresia Ika (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2025)
The study aimed to determine the carcass characteristics of local male pigs fed different energy sources. The research location is in Sasi Village, Kefamenanu District, North Central Timor Regency. The livestock used are 12 castrated local male pigs aged 12–16 weeks with a body weight range of 5–7 kg. The method used in the study is an experimental method using a completely randomised design (CRD) with 3 treatments and 4 replicates. The treatments tested were as follows: T1: 40% ground corn + 23% rice bran + 15% bran pollard + 22% fish meal; T2: 15% ground corn + 40% rice bran + 23% bran pollard + 22% fish meal; T3: ground corn 23% + rice bran 15% + pollard bran 40% + fish meal 22%. The variables observed in this study were slaughter weight, carcass weight, non-carcass weight, carcass percentage, and non-carcass percentage. The results showed that the treatments had no significant effect (P > 0.05) on slaughter weight, carcass weight, non-carcass weight, and carcass and non-carcass percentages of local male pigs in the growing phase. The slaughter weight for each treatment (T1, T2, and T3) was as follows: T1 was 6.867 kg, T2 was 7.936 kg, and T3 was 8.498 kg; the carcass weight for each treatment (T1, T2, and T3) was as follows: T1 was 3.466 kg, T2 at 4.115 kg, and T3 at 4.621 kg; the non-carcass weight for treatment T1 was 3.401 kg, T2 at 3.821 kg, and T3 at 3.886 kg; the carcass percentage for treatment T1 was 50.094%, T2 was 51.766%, and T3 was 52.674%; while the non-carcass percentages for treatments T1, T2, and T3 were 49.905%, 48.234%, and 47.325%, respectively. It can be concluded that the use of ground corn, rice bran, or bran pollard as an energy source feed results in carcass and non-carcass production of local male pigs in the growing phase that are not significantly different, although there is a higher tendency when using 40% bran pollard in the diet.